2018
DOI: 10.1002/hep.30041
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Growth Factor 15–Dependent and Bile Acid–Independent Promotion of Liver Regeneration in Mice

Abstract: The role of intestine-derived factors in promoting liver regeneration after partial hepatectomy (PHx) are not entirely known, but bile acids (BAs) and fibroblast growth factor 15 (Fgf15) that is highly expressed in the mouse ileum could promote hepatocyte proliferation. Fgf15 strongly suppresses the synthesis of BAs, and emerging evidence indicates that Fgf15 is important for liver regeneration. The mechanisms by which Fgf15 promotes liver regeneration are unclear, but Fgf15 may do so indirectly by reducing BA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 42 publications
1
38
0
Order By: Relevance
“…The Fgf15 –/– mice were raised with a 75%/25% mixed C57BL/6J/A129 background, respectively, because in a C57BL/6J background, knockout was embryonically lethal. TG mice were generated with a C57BL/6J background . At 8‐10 weeks of age, mice were fed either a control chow diet, 0.2% cholic acid (CA)‐containing diet (Cat.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Fgf15 –/– mice were raised with a 75%/25% mixed C57BL/6J/A129 background, respectively, because in a C57BL/6J background, knockout was embryonically lethal. TG mice were generated with a C57BL/6J background . At 8‐10 weeks of age, mice were fed either a control chow diet, 0.2% cholic acid (CA)‐containing diet (Cat.…”
Section: Methodsmentioning
confidence: 99%
“…TG mice were generated with a C57BL/6J background. (22) At 8-10 weeks of age, mice were fed either a control chow diet, 0.2% cholic acid (CA)-containing diet (Cat. # C1129; Sigma-Aldrich, St. Louis, MO), or a 2% cholestyramine-containing diet (Cat.…”
Section: Animals and Treatmentsmentioning
confidence: 99%
“…Also, in the ileum enterocyte, BA‐induced FXR‐dependent FGF15 induction has been identified as an important regulator of liver homeostasis, 44 regeneration after PH 45,46 and alcohol‐related liver injury 47 . Direct positive impact on hepatocyte (and cholangiocyte) cell cycle progression, 45,48 and indirect regulation through BA synthesis suppression 45 by FGF15 have been reported, although more complex effects of FGF15 appear to be involved in relation to NASH and fibrosis 49 . Thus, FXR‐dependent adaptive responses are crucial to protect the repairing liver after injury and to boost regenerative responses.…”
Section: Tgr5‐dependent Protective Responses Against Ba Overloadmentioning
confidence: 99%
“…FGF15 is secreted into portal circulation to function as a hormone [18]. In the liver, FGF15 can inhibit BA synthesis when binding to its receptor FGFR4, which is critical for BA homeostasis [19,20,21,22,23].…”
Section: Ileal Fxr Activation and Fgf15 Expression Was Upregulated Inmentioning
confidence: 99%
“…Animal experiments have shown that FGF15 is essential for hepatic homeostasis, and overexpression of FGF15/19 in the liver has beneficial effects on multiple liver diseases, including sclerosing cholangitis Page 20 of 30 [20], alcoholic fatty liver [22], and NAFLD [21,29]. In addition to its functions in hepatic metabolism, FGF15 has also been shown to contribute to liver regeneration [23,43,44]. In human, circulating FGF19 has been found to be increased in patients with biliary cirrhosis [45] and in patients with alcoholic hepatitis [46], which is accompanied with inhibition of BA synthesis.…”
Section: Gut Dysbiosis Can Be An Adaptive Response To Liver Injurymentioning
confidence: 99%